2015
DOI: 10.3389/fneur.2014.00282
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Traumatic Brain Injury for Human Vergence Dynamics

Abstract: Purpose: Traumatic brain injury involving loss of consciousness has focal effects in the human brainstem, suggesting that it may have particular consequences for eye movement control. This hypothesis was investigated by measurements of vergence eye movement parameters.Methods: Disparity vergence eye movements were measured for a population of 123 normally sighted individuals, 26 of whom had suffered diffuse traumatic brain injury (dTBI) in the past, while the remainder served as controls. Vergence tracking res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Interestingly, for vergence eye movements, there was a significant slowing of the divergence velocities relative to convergence velocities for both the control and dTBI groups, though no significant difference between the groups in this respect. This slowing of divergence relative to convergence on average replicates the result in studies of normal vergence behavior in Tyler et al ( 21 , 24 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, for vergence eye movements, there was a significant slowing of the divergence velocities relative to convergence velocities for both the control and dTBI groups, though no significant difference between the groups in this respect. This slowing of divergence relative to convergence on average replicates the result in studies of normal vergence behavior in Tyler et al ( 21 , 24 ).…”
Section: Discussionsupporting
confidence: 83%
“…The human participants consisted of 12 individuals (6 female) with dTBI and 11 age-matched controls (4 female) who met the criteria of corrected letter acuity of 20/50 or better in the best eye with no visible ocular abnormalities. They were recruited into the study on the basis of their participation in a companion behavioral study of eye movements ( 21 ). The individuals were assigned to the control group if they had no past history of dTBI events (12 individuals with ages ranging from 22 to 75; mean age: 33.3 ± 13.3).…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of studies have investigated the effects of head injuries and concussions on oculomotor,925,3237 vestibular,10,11,18,19,26 and reaction time 2730 (OVRT) performance. In this study we investigated whether combined OVRT measures can reliably distinguish concussed subjects from similarly aged controls in a population of high school students.…”
Section: Discussionmentioning
confidence: 99%
“…An innovative adjunct to current concussion assessment practice is to use high spatial and temporal resolution measurements of eye movement reflexes and responses to specific stimuli or tasks, generally known as video-oculography. Aberrations in eye movements in saccades, smooth pursuit, nystagmus, and vergence have proven to be informative indicators of brain injury,925 as have measurements of vestibular functions,10,11,18,19,26 and reaction time performance 2730…”
mentioning
confidence: 99%
“…40 A metaanalysis concluded that convergence insufficiency occurs in 37% of patients with mTBI. 18 Detailed studies have showed that dynamic vergence measures are reduced, 41 and vergence instability may be reflected in greater horizontal disconjugacy during naturalistic viewing. 42 Pursuit of a predictably moving target was reduced in some studies [43][44][45] but others found little change.…”
Section: Ocular Motor Dysfunction In Traumatic Brain Injurymentioning
confidence: 99%